Micron-Scale Distribution of Manganese in Allende and Implications for Constraining Conditions of Metamorphism - Dyl, Kathryn; Cleverley, J.; Bland, Philip; Hough, R.; Fisher, L.; Ryan, C. (Lunar and Planetary Science Institute, 2012)
We used Synchrotron x-ray analysis to investigate the micron-scale distribution of Mn in an Allende thin section. This technique may be useful in identifying minerals and processes that can be dated using the 53Mn-53Cr short-lived geochronometer.